Patient-reported adherence and persistence to topical treatments for actinic keratosis: a longitudinal diary study - Erntoft, Sandra; Norlin, J. M.; Pollard, C.; Diepgen, Thomas L. (British journal of dermatology, 2016)
Linked Comment: Cardwell and Feldman. Br J Dermatol 2016; 175:872.
Gesehen am 11.05.2020